Redox‐modulated colorimetric detection of ascorbic acid and alkaline phosphatase activity with gold nanoparticles. (2nd January 2020) - Lin, Liping; Luo, Yaxin; Chen, Qiushuang; Lai, Qingjiao; Zheng, Qiaoling
Abstract: Gold nanoparticles (AuNPs) exhibit characteristic absorption peaks in the ultraviolet visible region due to their special surface plasmon resonance effect. This characteristic absorption peak would change with the relative colour varying from wine red to orange‐yellow upon sequential addition of ascorbic acid (AA) into the mixture of AuNPs and Ag(I). Similar observations also could be found when the hydrolysis product of sodium l ‐ascorbyl‐2‐phosphate with alkaline phosphatase (ALP) was used as an alternative to AA. Results of structure characterization confirmed that the phenomena were due to the reduction of Ag(I) to Ag(0) on the surface of AuNPs and the formation of core‐shell AuNPs@Ag. Therefore, a colorimetric assay for rapid visual detection of AA and ALP based on redox‐modulated silver deposition on AuNPs has been proposed. Under the optimal experimental conditions, the absorbance variation ΔA522 nm /A370 nm of AuNPs was proportional to the concentration of AA (5–60 μmol/L) and ALP (3–18 U/L) with the corresponding detection limit of 2.44 μmol/L for AA and 0.52 U/L for ALP. The assay showed excellent selectivity towards AA and ALP. Moreover, the assay has been applied to detect AA and ALP activity in real samples with satisfying results.